A novel high-temperature-resistant polymeric material for cables and insulated wires via the ceramization of mica-based ceramifiable EVA composites. (23rd August 2016) - Li, Ying-Ming; Deng, Cong; Wang, Yu-Zhong
Abstract: A novel ethylene-vinyl acetate (EVA) composite for cables and insulated wires was prepared through incorporating glass powder (GP), mica powder (MP) and organo-modified montmorillonite (OMMT) into the EVA. Mechanical test showed that the tensile strength of EVA/GP/MP/OMMT composite with the ratio of 55/23/17/5 was 8.5 MPa, and its elongation at break was 790%; for its ceramics formed at 700 °C, the flexural strength reached to 11.8 MPa, and the volume resistivity was 3.87 × 10 11  Ω/cm. Thermal gravimetric analysis (TGA) showed that the initial thermal decomposing temperature of EVA/GP/MP/OMMT (55/23/17/5) was about 350 °C, and the residue was about 58.2%. The ceramics formed at high temperature were investigated by infrared spectroscopy (IR), scanning electron microscopy (SEM) and X-ray diffraction (XRD). The IR and XRD results demonstrated that the structure of MP was destroyed at high temperature, and a eutectic mixture was formed. SEM observation illustrated that the interface of the ceramics became fuzzy with increasing the GP, and the fluoramphibole crystals were formed at high temperature due to the presence of Na2 O, CaO, etc. All these experimental results demonstrated that the ceramization of mica-based EVA composite was achieved successfully, and the formed ceramics had excellent mechanical properties and insulativity.